Systematischer Literaturreview der Entrepreneurship Education Forschung zu Kompetenzen und Lehr- und Lernmethoden in der Sekundarstufe II - Büker, Ronja; Liszt-Rohlf, Verena; Kamsker, Susanne (Zeitschrift für Berufs- und Wirtschaftspädagogik)

The Many Faces of Sūrat al-Ikhlāṣ - Ghaffar, Zishan (Journal of the International Qur’anic Studies Association)
Although Sūrat al-Ikhlāṣ (Q 112) is one of the shortest sūrahs of the Qurʾān, it has led to an extensive commentary on its structure and content in Muslim exe-getical literature and in Western scholarship. This article takes the recent attempt to contextualize the sūrah in Western scholarship as a starting point and proposes new evidence for the nature of the religious milieu that shaped its form and content. It posits several “intertexts” of creedal expressions, which shed light on the discursive nature of the sūrah.
Keywords: Qurʾān; Christology; Niceno-Constantinopolitan Creed; Jacob of Serugh; Syriac Christianity; Credo

Dynamic effects of piezoelectric fan on the natural convection in a vertical channel - Boz, Özgün Alkim; Ezan, Mehmet Akif; Küçüka, Mustafa Serhan (International Journal of Technological Sciences)

Rezension: "Individuelles Handeln und Gemeinwohl. Eine interdisziplinäre Handlungstherorie im Kontext von Freiheit, Verantwortung und künstlicher Intelligenz" von Gerhard Tulodziecki - Herzig, Bardo (Zukunft - Die Diskussionszeitschrift für Politik, Gesellschaft und Kultur)

Langrezension zu Nathalie Bauers/Susanne Günthners/Juliane Schopfs (Hg.) 'Die kommunikative Konstruktion von Normalität in der Medizin' - Markewitz, Friedrich (Gesprächsforschung – Online Zeitschrift zur verbalen Interaktion)

Can You Go Home Again? Performance Assistance Between Boomerangs and Incumbent Employees - Grohsjean, Thorsten; Dokko, Gina; Yang, Philip (Organization Science)
Boomerangs, that is, rehires, should have advantages over other new hires when integrating into an organization due to their familiarity with the work context and their pre-existing relationships. However, research suggests that the effects of hiring boomerangs may not be straightforwardly positive. To better understand these effects, we investigate how boomerangs’ social integration into a work team differs from that of other new hires due to their pre-existing relationships and how those relationships shape their and incumbents’ competence and motivation to provide assistance for collective performance. We theorize and find that boomerangs, compared with new hires, exhibit more performance assistance toward incumbent former and incumbent new colleagues. In contrast, incumbent former colleagues do not direct their performance assistance toward boomerangs, contrary to our prediction, nor do incumbent new colleagues. This study contributes to the nascent literature on boomerangs and the literature on job mobility by finding evidence that prior relationships condition the behavior of both boomerangs and incumbents. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16685 .

A (Bounded) Preference for Rule Breakers - Wakeman, S Wiley; Yang, Philip; Moore, Celia (Academy of Management Discoveries)

Capabilities for the Strategic Alignment of Sustainability and Digitalization in Manufacturing: Insights from Theory and Practice - Kürpick, Christian; Schreiner, Nick; Krauß-Kodytek, Laura; Plaß, Sabrina; Scholz, Thorben; Kühn, Arno

Developing A Conceptual Model for Strategic Integration of Sustainability and Digitalization in Manufacturing. - Epp, Lena; Dörte, Foit; Kürpick, Christian; Plaß, Sabrina; Thorben, Scholz; Schreiner, Nick

Data and Social Worlds: How Data Science Education Supports Civic Participation and Social Discourse - Miller, Katherine M; Polman, Joseph L; Yoon, Susan A; Shim, Jooeun; Leung, Vivian Y; Nguyen, Yen; Rubin, Andee; Higgins, Traci; Karch, Jessica M; Hammerman, James KL; Matuk, Camillia; DesPortes, Kayla; et al. (Proceedings of the 18th International Conference of the Learning Sciences-ICLS 2024)

Salt‐Responsive Switchable Block Copolymer Brushes with Antibacterial and Antifouling Properties - Methling, Rafael; Greiter, Michael; Al‐Zawity, Jiwar; Müller, Mareike; Schönherr, Holger; Kuckling, Dirk (Macromolecular Bioscience)
Abstract A strategy for multifunctional biosurfaces exploiting multiblock copolymers and the antipolyelectrolyte effect is reported. Combining a polyzwitterionic/antifouling and a polycationic/antibacterial block with a central anchoring block for attachment to titanium oxide surfaces affords surface coatings that exhibit antifouling properties against proteins and allow for surface regeneration by clearing adhering proteins by employing a salt washing step. The surfaces also kill bacteria by contact killing, which is aided by a nonfouling block. The synthesis of block copolymers of 4‐vinyl pyridine (VP), dimethyl 4‐vinylbenzyl phosphonate (DMVBP), and 4‐vinylbenzyltrimethyl ammonium chloride (TMA) is achieved on the multigram scale via RAFT polymerization with good end group retention and narrow dispersities. By polymer analogous reactions, poly(4‐vinyl pyridinium propane sulfonate‐ block ‐4‐vinylbenzyl phosphonic acid‐ block ‐4‐vinylbenzyl trimethylammonium chloride) (P(VSP 64 ‐ b ‐PA 14 ‐ b ‐TMA 64 )) is obtained. The antifouling properties against the model protein pepsin and the salt‐induced surface regeneration are shown in surface plasmon resonance (SPR) experiments, while independently the antibacterial and antifouling properties of coated titanium substrates are successfully tested in preliminary microbiological assays against Staphylococcus aureus ( S. aureus ) and Escherichia coli ( E. coli ). This strategy may contribute to the development of long‐term effective antibacterial implant surface coatings to suppress biomedical device‐associated infections.
Keywords: antibacterial coatings; antipolyelectrolyte eﬀect; salt switchable polymers; zwitterionic brushes

Self-immolative polydisulfides and their use as nanoparticles for drug delivery systems - Völlmecke, Katharina; Kramer, Maurice; Horky, Corinna; Dückmann, Oliver; Mulac, Dennis; Langer, Klaus; Kuckling, Dirk (RSC Advances)
Over the last few decades, nanotechnology has established to be a promising field in medicine. A remaining dominant challenge in today's pharmacotherapy is the limited selectivity of active pharmaceutical ingredients and associated undesirable side effects. Controlled drug release can be promoted by smart drug delivery systems, which release embedded API primarily depending on specific stimuli. Consequently, also the microenvironment of tumor tissue can be used advantageously. Dithiothreitol (DTT) based self-immolative polydisulfides were synthesized that preferentially respond to pathologically increased glutathione (GSH) concentrations, as found in solid tumors. The synthesis with different degrees of polymerisation was investigated as well as the synthesis of a copolymer consisting of dithiothreitol and butanedithiol (BDT). Toxicity tests were carried out on pure polymers and their degradation products. The ability to degrade was examined at pathological and physiological glutathione concentrations in order to test the suitability of the polymer as a matrix for nanoparticulate carrier systems. In addition, the processability of one polymer into nanoparticles was investigated as well as the degradation behaviour with glutathione.

Regional variations in vaccination against COVID-19 in Germany - Bade, Verena; Schmitz, Hendrik; Tawiah, Beatrice Baaba (PLOS ONE)
Vaccination willingness against COVID-19 is generally perceived as low. Moreover, there is large heterogeneity across and within countries. As a whole, Germany has average vaccination rates compared to other industrialized countries. However, vaccination rates in the 16 different German federal states differ by more than 20 percentage points. We describe variation in vaccination rates on the level of the 400 German counties using data on all vaccinations carried out until December 2022. Around 52-72% of that variation can be explained by regional differences in demographic characteristics, housing, education and political party preferences. We find indications that the remaining part may be due to differences in soft factors such as risk aversion, trust in the German government, trust in science, and beliefs in conspiracy theories regarding the origins of the Corona virus. We conclude that improving the trust in science and the fight against conspiracy theories may possibly be effective tools to improve vaccination rates and effectively fight pandemics.

Multiple Normative Expectations and Interventions -Experimental Evidence on Whistleblowing Behaviour - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina
Normative expectations – beliefs about what others perceive as appropriate – have been shown to influence behavioural choices across various domains. We examine this concept in the context of whistleblowing, where potential whistleblowers face two competing norms: promoting fairness by reporting wrongdoing versus maintaining loyalty to peers by staying silent. We investigate how normative expectations about these two mutually exclusive actions affect reporting decisions. Specifically, we test whether providing information on the majority beliefs about either the appropriateness of whistleblowing, or of staying silent, or about both behaviours together, differentially affects the whistleblowing decision. Using an incentivized experiment with UK employees on Prolific, our study yields four key findings: First, employees are more likely to report misconduct when they believe that the majority considers whistleblowing to be appropriate. Second, they are less likely to blow the whistle when they believe staying silent is deemed appropriate. Third, this effect prevails for a particularly important subgroup: among employees who believe that the majority supports whistleblowing, the reporting probability increases substantially when they simultaneously expect that staying silent is deemed inappropriate. Fourth, providing information about both normative dimensions combined or only about the inappropriateness of staying silent significantly increases whistleblowing compared to the (no information) baseline and to information about whistleblowing appropriateness alone. These findings demonstrate the importance of normative expectations about both behavioural options for accurately predicting whistleblowing behaviour, and that social information interventions are most effective when they target behaviours where appropriateness beliefs about conflicting options are dispersed.
Keywords: Whistleblowing; Normative Expectations; Social Information Intervention; Social Norms; Economic Experiment

“I don’t believe that you believe what I believe”: an experiment on misperceptions of social norms and whistleblowing - Mir Djawadi, Behnud; Plaß, Sabrina; Loer, Sabrina
Social norms fundamentally shape economic decision-making, yet individuals often systematically misperceive what others think and do, potentially leading to suboptimal social outcomes. We examine how such misperceptions affect behaviour and whether correcting them can induce a behavioural change, using whistleblowing as an application. Through survey data and an incentivized laboratory experiment, we demonstrate that while a majority of individuals (>75%) privately support whistleblowing, almost half (45.92%) misperceive the majority’s view. Both personal normative beliefs and normative expectations strongly predict whistleblowing behaviour. Their alignment is particularly noteworthy: individuals who personally support whistleblowing are more likely to report misconduct when they believe others share their views. A social information intervention revealing the true distribution of peer support affects subgroups differently: while it increases whistleblowing behaviour among individuals who already personally favour reporting misconduct, there is no effect among those who are personally resistant to it. Still, given the relatively low cost of such social information interventions, they offer an economically viable means of achieving behavioural change in at least some of the targeted individuals.
Keywords: Social Norms; Normative Expectations; Personal Normative Belief; Misperceptions; Whistleblowing

Procrastination of learners in school and at universities - Klingsieck, Katrin B.; Grunschel, Carola (Zeitschrift für Entwicklungspsychologie und Pädagogische Psychologie)

Digitale Medien und die Produktion von Wissenschaft

Metalepsis in Radio Drama: Audionarratological Perspectives - Mildorf, Jarmila (Contemporanea: rivista di studi sulla letteratura e sulla comunicazione)

TS-SEP: Joint Diarization and Separation Conditioned on Estimated Speaker Embeddings - Boeddeker, Christoph; Subramanian, Aswin Shanmugam; Wichern, Gordon; Haeb-Umbach, Reinhold; Le Roux, Jonathan (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Keywords: Electrical and Electronic Engineering; Acoustics and Ultrasonics; Computer Science (miscellaneous); Computational Mathematics

Whitepaper: From HARA and TARA to Risk-Based Safety and Security Dependency Testing - Trentinaglia, Roman; Fockel, Markus; Pukrop, Matthias; Schaeffer, Tobias
Modern vehicles are becoming more connected and autonomous, and more software-defined in general. Such connectivity leads to security risks due to the increased attack surface for external intrusions. In addition, attacks can also lead to safety hazards as cars contain multiple safety-critical components. Therefore both safety and security must be considered in combination. In this whitepaper, we describe a tool-supported analysis method aligned with automotive standards to identify safety and security dependencies and automatically derive corresponding test cases. These test cases can be imported into the existing dSPACE tool chain to improve efficiency by reducing time-consuming manual work and susceptibility to errors. Thereby, our method brings together system design and testing phases to pave the way for an integrated safety and security-by-design life cycle in the automotive domain.